CHRONOLOGICAL STUDY OF SEDIMENTS FROM ALAMBARI RIVER, SÃO JOSÉ DOS CAMPOS, SÃO PAULO STATE, BRAZIL: IMPACTS OF INDUSTRIAL AND OIL REFINERY ACTIVITIES - Bonotto, Daniel Marcos [UNESP] (2022)
Several studies in Nuclear Geophysics have adopted the210Pb chronological method to determine sedimentation rates in hydrographic basins. In this paper, such technique was utilized to investigate sediments collected from the Alambari River, located in the vicinity of the Henrique Lage Refinery (Revap-Petrobras), in the municipality of São José dos Campos, São Paulo State, Brazil. This study was carried out in order to observe the potential anthropic influences of the refinery on the Alambari River sediments. For the collected sediments, analysis including loss on ignition (LOI), grain size, chemical composition, and sedimentation rates/sediment age were carried out, in this case, adopting the210Pb Constant Rate of Supply (CRS) model. The average sedimentation rate varied between 0.363 g/cm².year and 1.68 g/cm².year. Silica was identified as the main constituent in all three sediment cores analyzed in this study, with average concentrations of 41.63-82.58% and was correlated inversely with aluminum, iron and titanium, among other oxides. The X-ray fluorescence spectrometry also allowed identifying the presence of elements that could be associated with petroleum and its derivatives, such as palladium, nickel and vanadium, possibly indicating the contamination of sediments of the Alambari River by effluents or leaks due to the refinery's activities.